Effectively Converting Cane Molasses into 2,3-Butanediol Using Clostridiumljungdahlii by an Integrated Fermentation and Membrane Separation Process - Yuling Yang; Tingting Deng; Weifeng Cao; Fei Shen; Sijia Liu; Jing Zhang; Xinquan Liang; Yinhua Wan (Molecules, 2022)
Firstly, 2,3-butanediol (2,3-BDO) is a chemical platform used in several applications. However, the pathogenic nature of its producers and the expensive feedstocks used limit its scale production. In this study, cane molasses was used for 2,3-BDO production by a nonpathogenic Clostridium ljungdahlii. It was found that cane molasses alone, without the addition of other ingredients, was favorable for use as the culture medium for 2,3-BDO production. Compared with the control (i.e., the modified DSMZ 879 medium), the differential genes are mainly involved in the pathways of carbohydrate metabolism, membrane transport, and amino acid metabolism in the case of the cane molasses alone. However, when cane molasses alone was used, cell growth was significantly inhibited by KCl in cane molasses. Similarly, a high concentration of sugars (i.e., above 35 g/L) can inhibit cell growth and 2,3-BDO production. More seriously, 2,3-BDO production was inhibited by itself. As a result, cane molasses alone with an initial 35 g/L total sugars was suitable for 2,3-BDO production in batch culture. Finally, an integrated fermentation and membrane separation process was developed to maintain high 2,3-BDO productivity of 0.46 g·L−1·h−1. Meanwhile, the varied fouling mechanism indicated that the fermentation properties changed significantly, especially for the cell properties. Therefore, the integrated fermentation and membrane separation process was favorable for 2,3-BDO production by C. ljungdahlii using cane molasses.